Аналіз явищ масової комунікації: методологічний підхід - Косюк, Оксана М.; Kosyuk, O. М. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У публікації засвідчено, чим загальнофілософські методи відрізняються від конкретнонаукових і чому в царині масової комунікації найважливішими є структурний та семіотичний методи, а також контент- і герменевтичний аналізи. Принагідно з’ясовано, чим дослідження Клода Леві-Строса відрізняються від наукових шукань Володимира Проппа i чому перші спроби використання контент-аналізу пов’язані із християнством. In the article the author analyses, what way the common philosophic methods differ from scientific ones and why in area of mass communication major are structural and semiotic methods, and also content and hermeneutics analyses. It is found out, what researches of Claude Levi-Straus differ from the scientific searches of Volodymyr Propp; why the maiden attempts of the use of analysis of content are related to Christianity; what a sign grows into, when a value “grows” on to him; what signs remind tools; what discourses are coding non-stereotypical; whether it is possible after signs to define that cultures belong artistic creation; what even codes are in journalism and literature and why, for a paradox, exactly the high level of coding allows to use a literary word in the field of journalism as the most truthful source; whether those, who considers a sign the fig leaves of culture are rights; why a semiotic method is mostly used to discourses and texts, made after reception models, but the most perfect in mediasphere is a hermeneutics analysis.
The analysis of mass communication phenomenon: methodological approach
Keywords: метод; method; аналіз; analyses; структура; structure; семіотика; semiotics; знак; sign; код; code; інтерпретація; interpretation